Microtubule dynamics in interphase cells (The Rockefeller University Press, 1986)
The sites of microtubule growth and the kinetics of elongation have been studied in vivo by microinjection of biotin-labeled tubulin and subsequent visualization with immunocytochemical probes. Immunofluorescence and immunoelectron microscopy demonstrate that injected biotin-labeled subunits are incorporated into new segments of growth which are contiguous with unlabeled microtubules. Rapid incorporation occurs by elongation of existing microtubules and new nucleation off the centrosome. The growth rate is 3.6 micron/min and is independent of the concentration of injected labeled tubulin. This rate of incorporation together with turnover of existing microtubules leads to approximately 80% exchange in 15 min. The observed kinetics and pattern of microtubule turnover allow for an evaluation of the relevance of several in vitro models for steady-state dynamics to the in vivo situation. We have also observed a substantial population of quasi-stable microtubules that does not exchange subunits as rapidly as the majority of microtubules and may have specialized functions in the cell.